Biologics in Psoriasis: Updated Perspectives on Long-Term Safety and Risk Management - Al-Janabi A; Yiu ZZN (Psoriasis: Targets and Therapy, 2022)
A Al-Janabi,1,2 ZZN Yiu1,2 1Division of Musculoskeletal and Dermatological Sciences, School of Biological Sciences, Faculty of Biology, Medicine and Health, The University of Manchester, Manchester, UK; 2The Dermatology Centre, Salford Royal NHS Foundation Trust, Manchester NIHR Biomedical Research Centre, Manchester Academic Health Science Centre, Manchester, M6 8HD, UKCorrespondence: ZZN YiuDermatology Centre, Salford Royal Hospital, Stott Lane, Manchester, M6 8HD, UKEmail zenas.yiu@manchester.ac.ukAbstract: Biologics targeting Th1/Th17 cytokines have revolutionised psoriasis treatment. In addition to treatment effectiveness, it is important to define and understand the long-term risks of biologic therapy in order to guide therapy selection and minimise these risks for patients where possible. This review article summarises available evidence from trial data, observational studies and pharmacovigilance registries to explore key long-term risks of biologic treatment, and how these risks might be managed in clinical practice.Keywords: psoriasis, biologics, therapeutics, safety